DC and microwave characteristics of 20 nm T-gate InAlN/GaN high electron mobility transistor for high power RF applications. (September 2017) - Murugapandiyan, P.; Ravimaran, S.; William, J.; Ajayan, J.; Nirmal, D.
Abstract: The DC and microwave characteristics of 20 nm gate length (Lg ) InAlN/GaN High electron mobility transistor (HEMT) on SiC substrate with heavily doped source and drain region have investigated for both depletion mode (D-mode) and Enhancement mode (E-mode) operation using Synopsys TCAD tool. The simulation is performed at room temperature by using drift-diffusion model. The device having the features of recessed T - gate structure, InGaN back barrier and Al2 O3 passivated device surface. The proposed novel Lg = 20 nm, W = 2 × 40 μm D-mode (E-mode) HEMT exhibited a peak drain current density (Idmax ) of 2.7 (2.6) A/mm, transconductance (gm ) of 1.04 (1.63) S/mm, current gain cut-off frequency (ft ) of 310 (343) GHz and power gain cut-off frequency (fmax ) of 364 (236) GHz. The measured carrier mobility (μ), sheet charge carrier density (ns ) and breakdown voltage are 1580 (1615) cm 2 /V−s, 1.9 × 10 13 (1.93) Cm −2 and 10.7 (12.8) V respectively. The superlatives of the proposed HEMTs are bewitching competitor for future sub-millimetre wave high power RF VLSI circuit applications. Abstract : The DC and microwave characteristics of 20 nm gate length ( L g ) InAlN/GaN High electron mobility transistor ( HEMT ) on SiC substrate with heavily doped source and drain region have investigated for both depletion mode (D-mode) and Enhancement mode (E-mode) operation using Synopsys TCAD tool. The simulation is performed at room temperature by using drift-diffusion model. The device having the features of recessed T - gate structure, InGaN back barrier and Al 2 O 3 passivated device surface. The proposed novel L g = 20 nm, W = 2 × 40 μm D-mode (E-mode) HEMT exhibited a peak drain current density I dmax of 2.7 (2.6) [ A/mm ], transconductance g m of 1.04 (1.63) [ S/mm ], current gain cut-off frequency f t of 310 (343) GHz and power gain cut-off frequency f max of 364 (236) GHz. The measured carrier mobility( μ ), sheet charge carrier density (n s ) and breakdown voltage are 1580 (1615) ( cm 2 /V−s ), 1.9 × 10 13 (1.93) (Cm −2 ) and 10.7 (12.8) V respectively. The superlatives of the proposed HEMTs are bewitching competitor for future sub-millimeter wave high power RF VLSI circuit applications.